Pengaruh Komunikasi Antarpribadi Pelatih dan Atlet di desa senuro terhadap Latihan Siswa IKS PI kera sakti Cabang Olahraga Pencak Silat - Imam Ramdhani; Intan Putri; Nanda Syukerti (Universitas Dehasen Bengkulu, 2024)
This research was conducted to find out the influence of interpersonal communication between coaches and athletes in Senuro village on the training of iks Pi Kera Sakti students in the pencak silat sport. The aim of this research is interpersonal communication between coaches and athletes in Senuro village. The type of research used in this research is a quantitative approach. The data collection techniques used were interview, observation and documentation techniques. This research took place in West Senuro Village, South Ogan Ilir Indralaya Regency. The results of this research indicate that interpersonal communication between Coaches and Athletes in increasing team solidarity and performance is going well. Athletes can also respond directly to the content of the message by carrying out and implementing the content of the message, and the athlete feels encouraged, motivated and confident to carry out the movements taught by the coach during training. This is done in the form of communication between the coach and the athlete, such as the goals given for reinforcement or feedback received by the athlete and vice versa, messages conveyed by the coach, both verbal and non-verbal, channels, distractions and obstacles.